2020
DOI: 10.21203/rs.3.rs-117181/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contrasting heat stress response patterns of coral holobionts across the Red Sea suggest distinct mechanisms of thermal tolerance

Abstract: Corals from the northern Red Sea, in particular the Gulf of Aqaba (GoA), have exceptionally high bleaching thresholds approaching >5°C above their maximum monthly mean (MMM) temperatures. These elevated thresholds are thought to be due to historical selection, as corals passed through the warmer Southern Red Sea during re-colonization from the Arabian Sea. To test this hypothesis, we determined thermal tolerance thresholds of GoA versus Central Red Sea (CRS) Stylophora pistillata corals using the Coral Blea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 64 publications
7
33
0
Order By: Relevance
“…The Fv/Fm ED 50 is not an absolute measure of thermal tolerance, as the absolute thermal tolerance of a coral is likely to be affected by the prospective diel/seasonal heating and light regime among other factors. Still, our results, along with those from Voolstra et al (2020a) and Morikawa and Palumbi (2019), indicate some consistency in the response of corals to acute thermal assays and more prolonged thermal exposures and serve as evidence that acute thermal assays could provide realistic assessments of natural variance in the thermal tolerance of coral populations (Voolstra et al 2020b). As such, this approach could hold great promise as a standardized diagnostic to empirically assess environmental and evolutionary drivers of thermal tolerance across large scales and identify coral populations with the greatest chance of surviving future impacts of global warming.…”
Section: Discussionsupporting
confidence: 67%
“…The Fv/Fm ED 50 is not an absolute measure of thermal tolerance, as the absolute thermal tolerance of a coral is likely to be affected by the prospective diel/seasonal heating and light regime among other factors. Still, our results, along with those from Voolstra et al (2020a) and Morikawa and Palumbi (2019), indicate some consistency in the response of corals to acute thermal assays and more prolonged thermal exposures and serve as evidence that acute thermal assays could provide realistic assessments of natural variance in the thermal tolerance of coral populations (Voolstra et al 2020b). As such, this approach could hold great promise as a standardized diagnostic to empirically assess environmental and evolutionary drivers of thermal tolerance across large scales and identify coral populations with the greatest chance of surviving future impacts of global warming.…”
Section: Discussionsupporting
confidence: 67%
“…It did, however, decrease at 34.5°C, especially in the long-term experiments (Fig. 3B), indicating a sharp transition in resilience of the symbiont population, similar to the coral host, between 32°C and 34.5°C (41). In addition, 414 DEGs appeared in the 32°C treatment at T2 in the short-term experiment (Dataset S3), mainly as a down-regulation of genes involved in photosynthesis, indicating that reduced photosynthetic activity might be beneficial to the symbionts immediately after thermal stress, possibly to reduce the abundance of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 92%
“…In corals, fine-scale resolutions of Symbiodiniaceae assemblages often strongly correlate to host genotype (Gardner et al, 2019;Howells et al, 2020;Hume, D'Angelo, et al, 2018;Hume et al, 2020). However, if the Red Sea T. maxima populations are assumed to be a single well-connected, yet diverse population, this would suggest that the prevailing environmental conditions, which are also known to strongly influence coral-Symbiodiniaceae associations (Hume et al, 2020;LaJeunesse et al, 2010;Oliver & Palumbi, 2009;Smith et al, 2020;Terraneo et al, 2019;Varasteh et al, 2017;Voolstra, Valenzuela, et al, 2020;Ziegler et al, 2015), are the driving forces of the observed structure. Whether this relatively high clam-symbiont flexibility is a product of the location in which the algal symbionts reside within the host tissue (i.e., extracellularly in clams vs. intracellularly in corals) remains to be investigated.…”
Section: Panmictic Distribution Of Tridacna Maxima Suggests Environmentioning
confidence: 99%